Integration of Pancasila and Progressive Islam in Education for the SDGs - Developing Quality Student Character - Khosiah, Nur; Pantiwati, Yuni; Utomo, Dwi Priyo (CV. Bimbingan Belajar Assyfa, 2025)
In the era of globalization and modernization, education in Indonesia faces the challenge of developing students' character not only with extensive knowledge but also with strong moral values. The background of this research is the need to integrate the Pancasila ideology and progressive Islamic principles in education to achieve the Sustainable Development Goals (SDGs), particularly in developing quality student character. The main objective of this research is to explore how the integration of these two concepts can be effectively implemented in the education system to prepare an adaptive and ethical generation. The method used in this research is a qualitative approach with literature analysis and case studies of several educational institutions that have successfully implemented this integration. The results show that the integration of Pancasila and progressive Islam can produce students with more tolerant characters, global perspectives, and commitment to humanitarian values. The conclusion of this study emphasizes the importance of collaboration between educators, policymakers, and the community to create an educational environment that supports student character development that balances knowledge and morality. The implication of this research is that Indonesian education policy could further emphasize the importance of a holistic approach to learning to ensure students are not only prepared to face global challenges but also able to contribute positively to the nation and the world.